Religious Freedom and Mediation: Some Notes on Three New Initiatives in Indonesia - Ali-Fauzi, Ihsan (Interreligious studies and intercultural theology, 2022)
In recent years, Indonesia has experienced a decline in religious freedom. An increasingly popular strategy in dealing with this issue is mediation, which is perceived to be less costly, less divisive, and more lasting. While mediation has opened up new opportunities for strengthening religious freedom, it also has its own challenges. This article evaluates three initiatives in this direction. The first is the efforts of the local government to mediate disputes about houses of worship as evident in the recent case of the Yasmin Christian Church in Bogor City (West Java). Although the two conflicting parties finally agreed to relocate the church, both its process and end result leave behind potential legal issues that could emerge in the future. The second is the use of mediation by the Indonesia National Commission of Human Rights to resolve religious conflicts. While the Commission is relatively successful in pushing the local government to mediate the conflicts, the solutions it has achieved are not necessarily effective. The third is attempts at the institutionalization of interfaith mediation through the Interreligious Harmony Forum. Although the central government has supported these attempts, some structural problems continue to limit its progress.